2019
DOI: 10.5694/mja2.50117
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating recruitment strategies for AUSPICE , a large Australian community‐based randomised controlled trial

Abstract: Objectives To examine the effectiveness of different strategies for recruiting participants for a large Australian randomised controlled trial (RCT), the Australian Study for the Prevention through Immunisation of Cardiovascular Events (AUSPICE). Design, setting, participants Men and women aged 55–60 years with at least two cardiovascular risk factors (hypertension, hypercholesterolaemia, overweight/obesity) were recruited for a multicentre placebo‐controlled RCT assessing the effectiveness of 23‐valent pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Limitations are that such methods can be costly and time-consuming, with one study reporting that telephone recruitment resulted in 1680 h spent on the phone and a total cost of $79 USD per participant [40]. Mailing advertising materials was shown to have a similar response rate [40] while incurring lower costs, with one study citing costs of printing and postage to be around $52 USD per participant [41].…”
Section: Recruitment Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations are that such methods can be costly and time-consuming, with one study reporting that telephone recruitment resulted in 1680 h spent on the phone and a total cost of $79 USD per participant [40]. Mailing advertising materials was shown to have a similar response rate [40] while incurring lower costs, with one study citing costs of printing and postage to be around $52 USD per participant [41].…”
Section: Recruitment Strategiesmentioning
confidence: 99%
“…Studies have also reported advertisements on search engines, such as Google, to be an effective recruitment strategy, and may have similar costs when compared to advertisements on social media platforms [45]. Despite the known merits of online recruitment methods, it has also been identified that samples from social media strategies can be biased, reducing diversity in age, socioeconomic status, location and ethnic background, and often result in lower retention rates [40][41][42]45]. Thus, in designing an online recruitment strategy, researchers should consider the potential limitations of these methods and have strategies in place to ensure a representative sample [43].…”
Section: Recruitment Strategiesmentioning
confidence: 99%
“…After the exclusion of duplicates, our search identified 3069 studies for abstract screening, of which 132 met the criteria for full-text review. We identified 23 studies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] that satisfied the inclusion criteria after full-text review ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The true consent rate would be higher after accounting for the oversampling of younger people and men (e.g., consent was 7% for women aged 45-69 years), people with an outdated mailing address in the Medicare database (usually ~3%) or who did not return the consent form because they were ineligible to participate (e.g., due to ancestry or a previous melanoma, estimated at ~20%). Other populationbased research studies recruiting through the Medicare database have experienced consent rates less than 10% [41]. Our pilot study recruited participants from a database of people interested in cancer research and had 41% consent [42].…”
Section: Discussionmentioning
confidence: 99%